(untitled) (Bangladesh Journal of Animal Science, 2016)
The study was carried out to determine and compare the toxicological effects of raw jack beans (RJB), bambara groundnuts (RBG) and benne seeds (RBS) on organs of cockerels (Goldmine strain).Full fat soya was replaced with RJB, RBG and RBS at 25% and 50% levels, respectively. One hundred and forty (140) cockerels were randomly distributed into seven dietary groups in an eight week feeding trial. Antinutritional factors such as canavanine, haemagglutinin, trypsin inhibitor, tannin and phytate contents were analyzed in the plant seeds. At the end of eighth week, the birds were killed by cervical dislocation while the internal organs were quickly dissected out. The liver, kidney, pancreas and testis were thereafter preserved in 10% formalin solution. The tissues of the organs were trimmed, fixed in Bouins fixative for 24h, embedded in wax, sectioned at 6µm with microtome and finally stained with haematoxylin and eosin for histopathological examination. The livers of the birds fed 25% RJB and 50% RJB showed extensive multifocal and lymphocytic infiltration with necrosis of hepatocytes. Moreover, the pancreas of birds fed RBG and RJB based diets showed necrosis of glandular cells, lymphoid aggregates, thickening of the supporting stroma and multifocal interstitial lymphocytic infiltration. In the testes of birds fed 25% RJB and 50% RJB, there was extensive degeneration of the seminiferous tubular epithelia cells with widespread interstitial lymphocytic infiltrations of the stroma. The liver, pancreas, kidney and testes of birds fed RBS showed moderate lesions. It is concluded in this study that RJB showed more toxicity than RBG and RBS with respect to lesions in the organs, thus depicting a severe negative effect when fed to cockerels. There is therefore the need to detoxify the raw plant seeds with a view to enhancing their nutritive value in diets of cockerels. Bang. J. Anim. Sci. 2016. 45 (2): 18-23